2014
DOI: 10.1007/978-1-4939-0928-5_25
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Cytoplasmic and Nuclear Levels of Inflammatory Cytokines in Cancer Cells by Western Blotting

Abstract: Increased expression and cellular release of inflammatory cytokines, interleukin-8 (IL-8; CXCL8), and high mobility group box-1 (HMGB1) are associated with increased cell proliferation, angiogenesis, and metastasis during cancer progression. In prostate and ovarian cancer cells, increased levels of IL-8 and HMGB1 correlate with poor prognosis. We have recently shown that proteasome inhibition by bortezomib (BZ) specifically increases IL-8 release from metastatic prostate and ovarian cancer cells. In this chapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…These data showed that HMGB1 overexpression might be correlated with the development and progression of OS. These observations also support previous conclusions that increased expression HMGB1 is associated with increased cell proliferation, angiogenesis, and metastasis during cancer progression [15,33].…”
Section: Discussionsupporting
confidence: 90%
“…These data showed that HMGB1 overexpression might be correlated with the development and progression of OS. These observations also support previous conclusions that increased expression HMGB1 is associated with increased cell proliferation, angiogenesis, and metastasis during cancer progression [15,33].…”
Section: Discussionsupporting
confidence: 90%
“…Techniques for subcellular fractionation prior cytokine detection can distinguish nuclear and cytoplasmic localization [ 104 , 105 ]. Most of the cytokines are localized in the cytoplasm of the producing cell before secretion.…”
Section: Cytokine Detection Techniquesmentioning
confidence: 99%
“…HMGB1 is considered a biomarker for ovarian cancer [ 38 , 39 ] and increased levels of interleukin-8 protein (IL-8) and HMGB1 correlate with poor prognosis in prostate and ovarian cancer cells [ 125 ]. Targeting HMGB1 by RNA interference inhibits ovarian cancer growth and metastasis [ 126 ].…”
Section: The Function Of Hmgb Proteins and Other Redox Sensors Durmentioning
confidence: 99%